KOMPETENSI PEDAGOGIK KETELADANAN PADA PENDIDIKAN ANTIKORUPSI DI PROVINSI LAMPUNG - Zulaiha, Aida; Robandi, Babang (Universitas Muria Kudus, 2024)
This study aims to analyze the pedagogical competence required for character education development, particularly in PAK, and the importance of role modeling in its success. The research uses a descriptive analysis method on teaching modules and project documents based on PAK designed by teachers at the secondary education level in Lampung. The findings reveal that pedagogical competence must be supported by teachers' personality, social, and professional competencies. The integrity-based learning protocol, as part of the PAK module, is designed to instill values such as honesty, discipline, responsibility, and courage in students. Teachers' role modeling, demonstrated through integrity in and outside the classroom, is a key element in building an educational ecosystem of integrity. This study recommends strengthening pedagogical competence training to ensure the sustainability of PAK implementation in schools.